1998
DOI: 10.1212/wnl.50.4.909
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal malformation as a cause of familial febrile convulsions and subsequent hippocampal sclerosis

Abstract: These findings suggest a subtle, pre-existing hippocampal malformation that may facilitate febrile convulsions and contribute to the development of subsequent HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
130
3
10

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(157 citation statements)
references
References 42 publications
11
130
3
10
Order By: Relevance
“…However, there is no doubt that children with long-lasting lateralized febrile seizures are at risk for developing temporal lobe epilepsy (97), and magnetic resonance (MR) imaging has produced evidence of hippocampal injury after prolonged focal febrile seizures (100). However, another MR study found evidence of a subtle, preexisting hippocampal malformation as a cause of familial febrile seizures and subsequent hippocampal sclerosis (101). There is evidence demonstrating that mesial temporal sclerosis is both a result and a cause of seizures (102).…”
Section: Febrile Seizures and Type Of Later Epilepsymentioning
confidence: 99%
“…However, there is no doubt that children with long-lasting lateralized febrile seizures are at risk for developing temporal lobe epilepsy (97), and magnetic resonance (MR) imaging has produced evidence of hippocampal injury after prolonged focal febrile seizures (100). However, another MR study found evidence of a subtle, preexisting hippocampal malformation as a cause of familial febrile seizures and subsequent hippocampal sclerosis (101). There is evidence demonstrating that mesial temporal sclerosis is both a result and a cause of seizures (102).…”
Section: Febrile Seizures and Type Of Later Epilepsymentioning
confidence: 99%
“…The association between temporal lobe development abnormalities -including focal cortical dysplasia (FCD) -and MTS is also recognized [55][56][57] . Therefore, although MTS is more commonly seen as an acquired pathology, presence of hippocampal malformation as a substrate for further development of MTS and TLE is frequently questioned 55,56,58 .…”
Section: Temporal Lobe Epilepsy: Surgical Pathologymentioning
confidence: 99%
“…Therefore, although MTS is more commonly seen as an acquired pathology, presence of hippocampal malformation as a substrate for further development of MTS and TLE is frequently questioned 55,56,58 .…”
Section: Temporal Lobe Epilepsy: Surgical Pathologymentioning
confidence: 99%
“…Assim, por exemplo, mais recentemente tem sido considerada a possibilidade de essas alterações estruturais ocorrerem em familiares sem determinar manifestações clínicas de crises epilépticas 67 .…”
Section: Crise Febrilunclassified
“…Fernández et al 67 , em estudo realizado em duas famílias de sujeitos com epilepsia do lobo temporal e antecedente de crise febril, concluíram que a má-formação hipocampal é uma condição herdada que facilita a ocorrência das crises febris e não consequência destas. Além disso, a má-formação pode ser o ponto de partida para o desenvolvimento de esclerose hipocampal nos sujeitos com epilepsia do lobo temporal e antecedentes de crises febris.…”
Section: Crise Febrilunclassified